Conceptualizing businesses as social actors: A framework for understanding sustainability actions in small‐ and medium‐sized enterprises. (27th December 2018) - Westman, Linda; Luederitz, Christopher; Kundurpi, Aravind; Mercado, Alexander Julian; Weber, Olaf; Burch, Sarah Lynne
Abstract: Small‐ and medium‐sized enterprises (SMEs) can play a crucial role in advancing environmental and social well‐being. Yet various—often conflicting—explanations have been offered to clarify why SMEs pursue sustainability. Some arguments foreground possibilities of profit maximization, whereas others emphasize individual values and convictions. Research supporting such contradicting explanations is often biased towards large enterprises or small, innovative frontrunners. In this article, we examine the underlying drivers of social and environmental interventions of SMEs by exploring empirical data from a survey of over 1, 600 Canadian SMEs and complementary in‐depth interviews. We argue that sustainability actions of SMEs can be understood by viewing these firms as social actors—organizations that are shaped by individual values, internal and external interpersonal relationships, and are embedded in a social environment. This conceptualization directs attention to the full range of factors that shape sustainability engagement of SMEs and highlights frequently overlooked forms of sustainability‐oriented actions.